A prospective multicenter study to compare the precision of posttraumatic internal orbital reconstruction with standard preformed and individualized orbital implants. Issue 9 (September 2016) - Zimmerer, Rüdiger M.; Ellis, Edward; Aniceto, Gregorio Sanchez; Schramm, Alexander; Wagner, Maximilian E.H.; Grant, Michael P.; Cornelius, Carl-Peter; Strong, Edward Bradley; Rana, Majeed; Chye, Lim Thiam; Calle, Alvaro Rivero; Wilde, Frank; et al.
Abstract: Purpose: A variety of implants are available for orbital reconstruction. Titanium orbital mesh plates are available either as standard preformed implants or able to be individualized for the patient. The aim of this study was to analyze whether individualized orbital implants allow a more precise reconstruction of the orbit than standard preformed implants. Materials and methods: A total of 195 patients treated between 2010 and 2014 were followed up to 12 weeks after surgery. Of the patients, 100 had received standardized preformed and 95 individualized implants. The precision of orbital reconstruction with the different implants was determined by comparing the variances in the volume difference between the reconstructed and the contralateral orbit on the postoperative computed tomographic scans. Clinical volume-related parameters including globe position, vision, motility, and diplopia and surgical details including approach, timing and technique of implant modification, use of navigation, duration of surgery, as well as adverse events were documented. Results: Orbital reconstruction was significantly more precise when individualized implants were used. The same was seen with intraoperative navigation. An overlap in the use of individualized implants and navigation makes it difficult to attribute the improved precision to a single factor. Conclusion: This study demonstrated that individualization and navigation provide clinical benefit.